Unveiling BPS-induced colonic inflammatory injury in female mice: Integrated evidence from colon microbiome and metabolomic analyses - Han Liu; Yutian Wang; Lisi Wei; Jing Xu; Ruirui Wang; Ling-Guo Zhao; Zhi Tang (Ecotoxicology and Environmental Safety, 2025)
Bisphenol S (BPS), a common alternative to bisphenol A (BPA), is extensively utilized in the production of food-contact materials. Concerns about its potential health impacts have grown. However, the effects of BPS exposure on colonic physiology and its underlying molecular mechanisms remain poorly characterized. This study aimed to elucidate the effects of BPS exposure on gut health in female mice, focusing on investigate the role of colon microbiome and metabolome involved in these effects. The effects of BPS exposure on female mice were evaluated via oral gavage administration at doses of 0.05 mg/kg/day and 5 mg/kg/day for four weeks. Fecal samples and colon tissue collected from BPS exposure and control group were subjected to 16S rRNA gene sequencing and GC-MS based metabolomic analysis. Our results show that BPS exposure caused typical colonic damage, including shortened colon length, inflammatory responses, and weakened gut barrier function. Significant alterations were observed in gut microbiota composition, showing imbalances between harmful and beneficial bacteria, with a significant decrease in genera such as Paraprevotella, Ruminococcaceae NK4A214 group, Ruminiclostridium 6, and an increase in Escherichia, Helicobacter, Parasutterella, Erysipelatoclostridium, and Achromobacter. Moreover, metabolic pathways associated with colonic inflammation, including tryptophan metabolism, glutamate metabolism, and fatty acid metabolism, were significantly altered. Our findings demonstrate that BPS exposure compromises colonic homeostasis, induces dysbiosis of the gut microbiota, and disrupts colonic metabolic activity. These findings may provide critical molecular insights regarding disruption of gut integrity as a potential new pathway for mitigating human health risks associated with bisphenol S exposure.